Moderating Effect of Work-Life Balance on the Relationship between Human Resource Management Practices and Employee Happiness - Renusha, M. (Sabaragamuwa University of Sri Lanka, 2021)
This study is a systematic and scientific attempt to identify the moderating effect of the work-life balance of employees on the relationship between human resource management practices and employee happiness in the travel trade industries in Sri Lanka. The data was gathered from 379 Travel Trade employees under the survey strategy using a self-administered and structured questionnaire. Human resource management practices are considered the independent variable, employee happiness is the dependent variable, and work-life balance is considered a moderator variable while developing the conceptual framework. Two hypotheses were developed based on the theoretical and empirical accounts with regard to employee happiness. Accordingly, it was substantiated that there is a positive and significant relationship between Human Resource Management Practices and Employee Happiness. The Work-Life Balance significantly moderates the relationship between Human Resource Management Practices and Employee Happiness. The findings are significant in adding new knowledge to the literature and provide grounds to inquire about the importance of Human Resource Management Practices and Work-Life Balance in explaining the deep understanding of Employee Happiness.
Keywords: Employee happiness; Human resource management practices; Work-life balance